The reversal : a novel - Connelly, Michael, 1956- (New York : Little, Brown, 2010)
Mickey Haller, changing from defense attorney to prosecutor for this one important case, joins forces with Detective Harry Bosch when a child murderer is released on bail due to DNA evidence and needs to be retried, pitting Haller and Bosch against a slick defense attorney.
Keywords: Bosch, Harry (Fictitious character) -- Fiction; Police -- California -- Los Angeles -- Fiction; Murder -- Investigation -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction; Legal stories